Formation of Neologisms with English Component ‘Lockdown’ in Modern german - I. B. Akkuratova; M. I. Doynikova (Научный диалог, 2022)
During the pandemic, the German language lexicon was replenished with socially significant keywords, including anglicism ‘Lockdown’. The study of new formations on the basis of socially significant generating bases is important for studying the dynamics of word-formation processes in modern German, which determines the relevance of this work. The analysis of neoplasms with the ‘Lockdown’ component is carried out from the standpoint of the structural and semantic description of lexemes. The material for the analysis was neologisms from German printed online publications, as well as lexemes from the electronic database OWID. It is proved that the dominant nominations with the ‘Lockdown’ component are nouns, this phenomenon reflects the tendency towards substantiation and univerbation in the German language. Some adjectival composites have also been identified. Verbal nominations, represented by two lexemes with a structural feature: lockdownen  and  downlocken  (down locken) are described. It is shown that ‘Lockdown’ anglicism is able to combine with borrowed and native roots and morphemes, forming composites, derivatives and phrases. Examples of the creation of occasional contaminants formed by analogy with the word ‘Lockdown’ are given. It has been established that composites with a metaphorical meaning are designed to express the attitude of a linguistic personality to realities. The differentiation of neologisms-synonyms in semantic and stylistic terms is revealed.